PENGARUH DISIPLIN KERJA, MOTIVASI, DAN REMUNERASI TERHADAP KINERJA PEGAWAI KEPENDIDIKAN FAKULTAS TEKNIK UNIVERSITAS SEBELAS MARET SURAKARTA - arti, Sugi (Universitas Of Surakarta, 2019)
In this study, the author has research the effect of labor discipline, motivation and remuneration simultaneously on education employee’s performance. The hypothesis in this study are: Suspected of labor discipline, motivation and remuneration does not significantly influence to educational employee’s performance of used. Data in this research is primary data obtained from questionnaires distributed to respondents. The analysis technique this study using validity, reliability test, multiple linear regression test, t test, F test, coefficient of determination test. The results of data analysis in this study can be concluded that the labour discipline, motivation, and employee remuneration does not significantly influence to employee’s the educational performance in the Faculty of Engineering Universitas Sebelas Maret Surakarta.